THE INFLUENCE OF WORK-LIFE BALANCE ON EMPLOYEE RETENTION WITH JOB SATISFACTION AS A MEDIATING VARIABLE: A CASE STUDY ON EMPLOYEES OF PT KAI DIVRE II WEST SUMATRA - Abdi Pratama; Laura Syahrul; Rahmi Fahmy (RADJA PUBLIKA, 2025)
Facing employee retention challenges, this study aims to analyze the influence of Work Life Balance (WLB) and Job Satisfaction (JS) on Employee Retention (ER), and to examine the mediating role of JS in the WLB and ER relationship. The retention problem was identified at PT Kereta Api Indonesia (Persero) Regional Division II West Sumatra, marked by fluctuating turnover rates and indications of issues with WLB and job satisfaction. This study used a quantitative approach with an explanatory design. Primary data were collected via questionnaires distributed to all employees of PT KAI Regional Division II West Sumatra. The study involved 227 employees as a sample, selected through simple random sampling from a total population of 552. The data were processed using Partial Least Square-Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. Testing was conducted on the measurement model (validity and reliability) and the structural model (hypothesis testing). The results show that WLB has a positive and significant effect on JS (path coefficient 0.991; p<0.001). JS also has a positive and significant effect on ER (path coefficient 1.575; p<0.001). However, the direct effect of WLB on ER was not significant (path coefficient -0.612; p=0.328). Crucially, JS was found to fully mediate the relationship between WLB and ER, with a positive and significant indirect effect. The model demonstrated strong predictive capability, evidenced by R 2 values of 0.982 for JS and 0.987 for ER. This research concludes that improving WLB indirectly enhances ER by creating higher JS, which is a key factor in retaining talent.